An Induced Mutation in HvRECQL4 Increases the Overall Recombination and Restores Fertility in a Barley HvMLH3 Mutant Background - Arrieta, Mikel; Macaulay, Malcolm; Colas, Isabelle; Schreiber, Miriam; Shaw, Paul D.; Waugh, Robbie; Ramsay, Luke (Frontiers in Plant Science, 2021)
Plant breeding relies on the meiotic recombination or crossing over to generate the new combinations of the alleles along and among the chromosomes. However, crossing over is constrained in the crops such as barley by a combination of the low frequency and biased distribution. In this study, we attempted to identify the genes that limit the recombination by performing a suppressor screen for the restoration of fertility to the semi-fertile barley mutant desynaptic10 (des10), carrying a mutation in the barley ortholog of MutL-Homolog 3 (HvMLH3), a member of the MutL-homolog (MLH) family of DNA mismatch repair genes. des10 mutants exhibit reduced recombination and fewer chiasmata, resulting in the loss of obligate crossovers (COs) leading to chromosome mis-segregation. We identified several candidate suppressor lines and confirmed their restored fertility in an Hvmlh3 background in the subsequent generations. We focus on one of the candidate suppressor lines, SuppLine2099, which showed the most complete restoration of fertility. We characterized this line by using a target-sequence enrichment and sequencing (TENSEQ) capture array representing barley orthologs of 46 meiotic genes. We found that SuppLine2099 contained a C/T change in the anti-CO gene RecQ-like helicase 4 (RECQL4) resulting in the substitution of a non-polar glycine to a polar aspartic acid (G700D) amino acid in the conserved helicase domain. Single nucleotide polymorphism (SNP) genotyping of F3 populations revealed a significant increase in the recombination frequency in lines with Hvrecql4 in the Hvmlh3 background that was associated with the restoration of fertility. The genotyping also indicated that there was nearly double the recombination levels in homozygous Hvrecql4 lines compared to the wild type (WT). However, we did not observe any significant change in the distribution of CO events. Our results confirm the anti-CO role of RECQL4 in a large genome cereal and establish the possibility of testing the utility of increasing recombination in the context of traditional crop improvement.